Latihan Mindfulness untuk Mengurangi Fear of Missing Out terhadap Sosial Media di SDN 1 Serdang - Siti Zahra Bulantika; Rizka Puspita Sari; Sa’adah Sa’adah (Pedagogia: Jurnal Ilmiah Pendidikan Dasar Indonesia, 2021)
The use of social networking sites (SNS) has grown and the use of social networking sites has become an integral part of everyday life. The use of social networking sites in Indonesia ranks sixth in the world with 112 million users of social networking sites. Consumption of social networking sites (SNS) certainly has an impact on the lives of individuals in the future, both positive and negative impacts. Although since the beginning the internet has offered various conveniences to its users such as speeding up individual work, media literacy, it will be worrying if it is not used wisely because it can have negative impacts such as fear of being out of date. This study aims to test the effectiveness of group counselling with mindfulness exercises in reducing the fear of missing out. The research method used is quantitative. The type of research used is experimental research with pretest-posttest control group design with repeated measurement model. The results of this study indicate that group counselling using mindfulness can reduce students' fear of missing out. In addition, other factors were found that could affect the level of students' fear of being out of date, namely how to interpret situations, beliefs and emotions. Thus, it can be concluded that group counselling using mindfulness can be used to intervene in students' fears of being left behind.